The "others" and us. Sameness and otherness. Experiences and reflections on the method of historical Anthropology (Quinto Sol, 2017)
Text of the keynote address by Ana María Lorandi delivered in the Second International Congress "The indigenous peoples of Latin America. Advances, perspectives and challenges". Santa Rosa, La Pampa, September 2016.
Keywords: otherness; indigenous peoples; method; anthropology